Analisis Peran Akumulasi Modal dalam Pertumbuhan Ekonomi: Faktor-Faktor Pendorong Pertumbuhan Ekonomi di Indonesia - Herlina Reva Carita; Haura Khalisa Hakim; Raden Naufal Hilmi Saputra; Ni Komang Mia Fabiola; Izzan Shulhan Albar; Vanessa Azahra Rohman; Ahmad Setiawan Nuraya (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
Economic growth is a complex process influenced by various factors, one of which is capital accumulation. Capital accumulation plays a crucial role in increasing production capacity, creating employment opportunities, and enhancing labor productivity. This study analyzes the role of capital accumulation in Indonesia’s economic growth by highlighting key factors contributing to national output expansion. Using the growth accounting approach and neoclassical growth theory, this research confirms that while capital accumulation contributes to per capita income growth, long-term economic growth remains dependent on efficient resource allocation and productivity improvements through innovation and human capital development. The Cobb-Douglas production model is applied to understand the relationship between capital, labor, and output in determining economic growth rates. The findings indicate that countries with higher savings and investment rates tend to experience faster economic growth. Therefore, economic policies focusing on increasing investment, strengthening human capital, and optimizing resource allocation are key factors in accelerating Indonesia’s economic growth.